Social Responsibility of Alternative Media and Indian Democracy - Tyagi, Priyanka; Pathak, Charu Chandra (Journal of Advanced Research in Journalism & Mass Communication, 2017)
Media always considered as fourth pillar of democracy. India has the largest democracy in the world, which usually put all its efforts in restoring the faith of masses in the system. Media being its driving force always supported or criticised time to time. Media constantly showed their presence in Indian democracy. Media not only performed their surveillance function but they also cater their duty of social responsibility perfectly. With the advent of new technologies the traditional media also shifted towards a relatively new alternative media that is (social media). Democracy also faces various crisis time to time and media always tried to find a path to overcome those crisis. Alternative media being the media of masses and by the masses have the factor of immediacy and proximity more than any traditional form of media, due to which it can circulate any piece of information rapidly as compare to radio and television as well. This paper actually examines that how this alternative media is performing their duty of social responsibility and how and what they are adding, towards Indian democracy. This research is based on qualitative research approach. Researcher would find out the role of alternative media towards democracy. How to cite this article: Tyagi P, Pathak CC. Social Responsibility of Alternative Media and Indian Democracy. J Adv Res Jour Mass Comm 2017; 4(3&4): 141-145. DOI: https://doi.org/10.24321/2395.3810.201703